Developing framework for natphoric computer-aided web-based kansei engineering / Mohammad Bakri Che Haron - Che Haron, Mohammad Bakri (2013)
Sophisticated consumers and high cornpetitive environment has forced designers and manufacturers to realize the importance of consumers emotion in creative product design. The design must be able to incorporate high acceptance and have persuasive power. Kansei Engineering (KE) is a technology that provides an insight into consumers psychological feelings when interacting with a product. KE is able to capture and determine the relationship between these feelings with product characteristics. These characteristics are then translated into the design and creation of products that can entice consumers to buy the product, hence increasing the rnarketability of the product in a highly competitive market. KE technological process generally consists phases; determination of specific domain and target market; Kansei evaluation; Kansei analysis, and formulating design guideline based on the interpretation of the data analysis. KE analysis' and interpretation requires a Kansei expert to deterrnine a set of related Kansei Words that identifies significant consumer and product relationship factor. However, there are not many kansei experts in the world today and there is no rule of thurnb or specific guide in the process. In this research, Natphoric algorithm is used in order to simulate how the experts find the significant factor of emotions. The Natphoric algorithm learns the process done by training with sets of training data from previous KE research works. This research proposes a Natphoric algorithrn to capture and simulate the expert kansei knowledge. The Natphoric algorithm is formulated to handle the complexity and flexibility in KE. To realize the development of computer-aided KE system, a framework for automated KE is designed. The designed framework incorporated a step-by-step technique of the use of 4I<:E Type 1 and automate the word classification process that usually requires expertise in KE. A prototype is developed to test the framework. Result shows that the automated KE prototype is able to produce similar result with the expert. The research outcome will benefit the product inventors and designers, especially in Malaysia, where there is in need of a good design rnethod to produce innovative product. The invention of this system will help to boost the movement towards achievement of the objectives.